Chapter 2 Freedom of speech in the age of digitalisation - Menkes, Jerzy (Taylor & Francis, 2022)
The author analyses one of the ‘Four Freedoms’—the freedom of speech—which is closely connected to political rights. Digitalisation has created a number of opportunities for ‘speech’ and reduced the barriers in human communication and thought transfer. However, digitalisation is also associated with threats to freedom of speech and the wrong use of it. In this chapter, a legal analysis of the contemporary content of freedom of speech is conducted and the opportunities and threats to this freedom in the age of digitalisation are examined. Moreover, representative national regulations of the EU member states and the USA are presented. The standard set by the ‘community of values’ is confronted with Poland’s practice. The DSA and Digital Market Act are assessed in terms of opportunities and threats to the freedom of speech.